Corrosion protective poly(o-toluldine) coatings on copper - Shinde, V.; Sainkar, S. R.; Patil, P. P. (Corrosion Science, 2005)
This study examines the use of poly(o-toulidine) (POT) coatings for corrosion protection of copper (Cu) in an aqueous solution of 3% NaCl. The POT coatings were synthesized on Cu substrates under cyclic voltammetric conditions from an aqueous solution of sodium oxalate. The resulting, POT coatings were uniform, shiny and strongly adherent to the Cu substrates. These coatings were characterized by cyclic voltammetry (CV), UV-visible absorption spectroscopy, Fourier transform infrared (FTIR) spectroscopy and scanning electron microscopy (SEM). The ability of POT to serve as a corrosion protective coating for Cu was examined by potentiodynamic polarization measurements and CV. The results of this study clearly reveal that the POT acts as corrosion protective coating on Cu and reduces the corrosion rate of Cu almost by a factor of 40. (c) 2004 Elsevier Ltd. All rights reserved.
Keywords: Conducting polymer coatings; Copper; Corrosion resistant coatings; cyclic voltammetry; poly(o-toluidine) coatings

Electrochemical synthesis and corrosion protection properties of poly(o-toluidine) coatings on low carbon steel - Shinde, V.; Sainkar, S. R.; Patil, P. P. (Journal of Applied Polymer Science, 2005)
Uniform and strongly adherent poly(o-toluidine) (POT) coatings have been synthesized on low carbon steel (LCS) substrates by electrochemical polymerization (ECP) of o-toluidine under cyclic voltammetric conditions from an aqueous sodium tartrate solution. Cyclic voltammetry (CV), UV-visible absorption spectroscopy, Fourier transform infrared spectroscopy (FTIR), X-ray diffraction (XRD) measurements, and scanning electron microscopy (SEM) were used to characterize these coatings, which indicates that the sodium tartrate is a suitable medium for the ECP of o-toluidine and it occurs without noticeable dissolution of LCS. Corrosion protection properties of the POT coatings were evaluated in aqueous 3% NaCl by the potentiodynamic polarization measurements and CV. The result of the potentiodynamic polarization demonstrates that the POT coating has ability to protect the LCS against corrosion. The corrosion potential was about 334 mV more positive in aqueous 3% NaCl for the POT-coated LCS than that of bare LCS and reduces the corrosion rate of LCS almost by a factor of 50. (c) 2005 Wiley Periodicals, Inc.
Keywords: conducting polymers; Corrosion resistant coatings; cyclic voltarnmetry; Electrochemical polymerization; FT-IR; Poly(o-toluidine); UV-vis spectroscopy

Formation of BaCrO4 nano crystallites within thermally evaporated sodium bis-2-ethylhexyl-sulfosuccinate and stearic acid thin films - Rautaray, D.; Sinha, K.; Sainkar, S. R.; Pasricha, R.; Pavaskar, N. R.; Sastry, M. (Journal of the American Ceramic Society, 2005)
This paper describes the growth of barium chromate (BaCrO4) nanocrystallites within thermally evaporated thin films of stearic acid (StA) and sodium bis-2-ethylhexyl-sulfosuccinate by a process of Ba2+ ion entrapment followed by in situ reaction CrO42- ions. Dense spherical assemblies of BaCrO4 nanocrystallites of very uniform size (similar to50 nm) were obtained within the two different host matrices. The spherical assemblies were composed of smaller (ca. 5-10 nm size) BaCrO4 crystals indicating that efficient size control over crystal size may be exercised by the matrix. Contact angle measurements of the BaCrO4-StA and BaCrO4-sodium bis-2-ethylhexyl-sulfosuccinate films indicated that they were hydrophobic, thus pointing to the possible role of hydrophobic interaction between the StA and sodium bis-2-ethylhexyl-sulfosuccinate monolayer-covered BaCrO4 crystals in the assembly process.

Miscibility of chitosan-hydroxyethylcellulose blends in aqueous acetic acid solutions at 35 degrees C - Wali, A. C.; Naidu, B. V. K.; Mallikarjuna, N. N.; Sainkar, S. R.; Halligudi, Shivaraj B.; Aminabhavi, Tejraj M. (Journal of Applied Polymer Science, 2005)
The miscibility of blends of chitosan and hydroxyethylcellulose in a 2% acetic acid solution was studied by viscometry, densitometry, and refractometry at 35 degrees C. The data suggest that the blends were completely miscible in all proportions. Further, the membranes were fabricated from concentrated blend solutions. The solid-state compatibility of the blends was confirmed by scanning electron microscopy. (c) 2005 Wiley Periodicals, Inc.
Keywords: blends; miscibility; refractive index; viscosity

Novel low-temperature synthesis of nanosized NiZn ferrite - Verma, S.; Pradhan, S. D.; Pasricha, R.; Sainkar, S. R.; Joy, Pattayil Alias (Journal of the American Ceramic Society, 2005)
Nanosized NiZn ferrite powder is synthesized by a low-temperature method, using a unique combination of citric acid and glycine. An appropriate molar ratio of both citric acid and glycine offers a low-temperature synthetic route by incorporating the complexation behavior of citric acid and the combustion nature of glycine. Thermal decomposition/controlled autocatalytic combustion of the composite gel occurs at a low temperature of around 175 degrees C, with the evolution of a large amount of gases. Transmission electron microscopic studies showed that the average particle size of the ferrite obtained is similar to 2.5 nm, with a narrow size distribution. Uniformly distributed fine-grained microstructure with low porosity is obtained for a sample sintered at 1000 degrees C.

Photoluminescent core-shell particles of organic dye in silica - Ethiraj, Anita S.; Hebalkar, Neha; Kharrazi, Sharmin; Urban, J.; Sainkar, S. R.; Kulkarni, S. K. (Journal of Luminescence, 2005)
Using a single silica precursor, Rhodamine 6G organic dye molecules have been entrapped in silica particles resulting into core-shell particles of similar to 500 nm diameter. Energy dispersive X-ray analysis, X-ray photoelectron spectroscopy and transmission electron microscopy analysis reveals that dye molecules are trapped inside the silica particles. Photoluminescence investigations show that highly luminescent and photostable core-shell particles are formed. Such core-shell particles can be easily suspended in water and would be useful for a variety of applications. However, there is a blue shift in the photolumineseence wavelength in case of core-shell particles compared to bare dye powder sample. (c) 2004 Elsevier B.V. All rights reserved.
Keywords: core-shell; Luminescence; Nanoparticles; photoemission; RH06G dye; tetraethylorthosilicate (TEOS)

Simple oxalate precursor route for the preparation of barium-strontium titanate: Ba1-xSrxTiO3 powders - Khollam, Y. B.; Deshpande, S. B.; Potdar, H. S.; Bhoraskar, S. V.; Sainkar, S. R.; Date, Sadgopal K. (Materials Characterization, 2005)
A simple one-step cation-exchange reaction between the stoichiometric solutions of ammonium titanyl oxalate (ATO) and barium hydroxide+strontium nitrate at room temperature (RT) is investigated successfully for the quantitative precipitation of barium-strontium titanyl oxalate (BSTO): Ba1-xSrxTiO(C2O4)(2).4H(2)O (x=0.25) precursor powders with nearly theoretical yield (greater than or equal to99%). The pyrolysis of BSTO at 730degreesC/4 h in air produced barium-strontium titanate (Ba1-xSrxTiO3; BST) powders. The characterization studies on BSTO and BST powders by using various physico-chemical techniques: micro- and chemical analysis, differential thermal analysis (DTA)/thermo-gavimetric analysis (TGA), XRD, FTIR, X-ray fluorescence (XRF) and scanning electron microscopy (SEM) revealed that the powders formed are cubic, highly pure, stoichiometric and sub-micron-sized with nearly uniform size and shape distribution. The ceramic compacts obtained by sintering the BST pellets at 1300degreesC/4 It showed density similar to95%, dielectric constant epsilon(Tc)similar to9500, tan delta-0.15% and T(C)similar to32 degreesC. (C) 2004 Elsevier Inc. All rights reserved.
Keywords: barium-strontium titanate; barium-strontium titanyl oxalate; permittivity; XRF

Study of correlation of structural and surface properties with electrochemical behaviour in carbon aerogels - Hebalkar, Neha; Arabale, G.; Sainkar, S. R.; Pradhan, S. D.; Mulla, Imtiaz S.; Vijayamohanan, K.; Ayyub, P.; Kulkarni, S. K. (Journal of Materials Science, 2005)
Carbon aerogel is a promising material for electrochemical double layer capacitors. In this paper carbon aerogels prepared by subcritical drying method are investigated for the change in the structure and surface properties at different pyrolysis temperatures. The important relations between structure, morphology, surface area and electrical properties were studied using X-ray diffraction (XRD), Fourier transform infrared (FTIR) spectroscopy, scanning electron microscopy (SEM), surface area measurement and cyclic voltametry. It is shown that structure and the surface functional groups play important role in enhancement of electrochemical capacitance. The specific capacitance achieved was 114 F/gm which is quite large value for subcritically prepared carbon aerogels without any kind of activation process. (c) 2005 Springer Science + Business Media, Inc.

Formation of poly(o-anisidine) coatings on copper from aqueous salicylate solution - Chaudhari, Sudeshna; Mandale, A. B.; Patil, K. R.; Sainkar, S. R.; Patil, P. P. (Surface & Coatings Technology, 2006)
Poly(o-anisidine) coatings have been electrosynthesized by using cyclic voltammetry on copper from an aqueous salicylate medium. Cyclic voltammetry, UV-visible absorption spectroscopy, Fourier transform infrared spectroscopy, scanning electron microscopy and X-ray photoelectron spectroscopy were used to characterize these coatings, which indicates that the aqueous salicylate solution is a suitable medium for the electrochemical polymerization of o-anisidine on copper substrate. Cyclic voltammetry accompanied by the X-ray photoelectron spectroscopy was used to characterize the surface modifications induced by polarizing the copper substrate in the aqueous salicylate solution (without monomer). It was shown that the polarization of the copper in the aqueous salicylate medium results into the passivation of its surface via the formation of Cu(2)O and/or copper salicylate complex. It was found that the electrochemical polymerization of o-anisidine takes place after the passivation of the copper substrate via fort-nation of Cu(2)O and/or copper salicylate complex and results into the formation of shiny, uniform and strongly adherent poly(o-anisidine). The optical absorption spectroscopy reveals the formation of emraldine salt form of poly(o-anisidine). This study offers an electrochemical polymerization recipe to synthesize strongly adherent poly(o-anisidine) coating on copper from aqueous media for possible use in corrosion protection application. (c) 2005 Elsevier B.V. All rights reserved.
Keywords: conducting polymers; Copper; corrosion protective coatings; cyclic voltammetry; poly(o-anisidine) coatings

Synthesis of corrosion inhibitive poly(2,5-dimethylaniline) coatings on low carbon steel - Shinde, V.; Sainkar, S. R.; Gangal, S. A.; Patil, P. P. (Journal of Materials Science, 2006)
An attempt has been made towards the synthesis of strongly adherent poly(2,5-dimethylaniline) coatings on low carbon steel substrates, with an objective of examining the possibility of using this polymer for corrosion protection of steel in chloride environment. In this work, the poly(2,5-dimethylaniline) coatings were synthesized by electrochemical polymerization of 2,5-dimethylaniline using sodium salicylate as a supporting electrolyte. The characterization of these coatings was carried out by cyclic voltammetry, UV-visible absorption spectroscopy, Fourier transform infrared spectroscopy and scanning electron microscopy. The results of these characterizations indicate that the aqueous salicylate solution is a suitable medium for the electrochemical polymerization of 2,5-dimethylaniline to generate strongly adherent and smooth poly(2,5-dimethylaniline) coatings on low carbon steel substrates. The performance of poly(2,5-dimethylaniline) as protective coating against corrosion of low carbon steel in aqueous 3% NaCl was assessed by the open circuit potential and the potentiodynamic polarization measurements. The potentiodynamic polarization measurement reveals that the poly(2,5-dimethylaniline) coating increases the corrosion potential and reduces the corrosion rate of low carbon steel almost by a factor of 50. This study clearly ascertains that the poly(2,5-dimethylaniline) has outstanding capability to protect low carbon steel against corrosion in chloride environment. (c) 2006 Springer Science + Business Media, Inc.

Anticorrosive properties of electrosynthesized poly(o-anisidine) coatings on copper from aqueous salicylate medium - Chaudhari, Sudeshna; Sainkar, S. R.; Patil, P. P. (Journal of Physics D-Applied Physics, 2007)
Poly( o-anisidine) ( POA) coatings were electrosynthesized on copper ( Cu) from an aqueous solution containing o-anisidine and sodium salicylate by using cyclic voltammetry, galvanostatic and potentiostatic modes. The extent of corrosion protection offered by these coatings to Cu in aqueous 3% NaCl solution was evaluated by the open circuit potential measurements, potentiodynamic polarization technique and electrochemical impedance spectroscopy. Potentiodynamic polarization and electrochemical impedance spectroscopy studies reveal that the POA acts as a protective layer on Cu against corrosion in 3% NaCl solution. The positive shift in the corrosion potential for the POA-coated Cu indicates the protection of the Cu surface by the POA. The POA coating synthesized by using cyclic voltammtery, galvanostatic and potentiostatic modes reduces the corrosion rate of Cu almost by a factor of 100, 100 and 7, respectively. The cyclic voltammetry was proved to be the better mode to adopt for the synthesis of more compact and strongly adherent POA coatings on Cu. The coatings synthesized by this mode were characterized by cyclic voltammetry, UV-visible absorption spectroscopy, Fourier transform infrared spectroscopy and scanning electron microscopy. It was found that the electrochemical polymerization of o-anisidine on Cu takes place after the passivation of its surface via the formation of Cu2O and/or copper salicylate complex and results in the generation of shiny, uniform and strongly adherent POA coatings. The optical absorption spectroscopy reveals the formation of the emeraldine salt form of POA. The results of this study clearly ascertain that the POA has outstanding potential to protect Cu against corrosion in a chloride environment.

Highly photostable dye entrapped core-shell particles - Ethiraj, Anita S.; Kharrazi, Sharmin; Hebalkar, Neha; Urban, J.; Sainkar, S. R.; Kulkarni, S. K. (Materials Letters, 2007)
Organic dye namely Coumarin 7 has been entrapped in silica particles using a single silica precursor viz. tetraethylorthosilicate. Both bare Coumarin 7 dye and dye incorporated core-shell particles were studied. Investigations of these core-shell composites were carried out using different characterization techniques such as energy dispersive X-ray analysis, X-ray photoelectron spectroscopy and transmission electron microscopy. It has been shown that the photostability of dye molecules is improved along with an increase in photoluminescence. (c) 2007 Elsevier B.V. All rights reserved.
Keywords: core-shell; coumarin 7 dye; Luminescence; photostability; tetraethylorthosilicate

Poly(o-ethylaniline) coatings for stainless steel protection - Chaudhari, Sudeshna; Sainkar, S. R.; Patil, P. P. (Progress In Organic Coatings, 2007)
The poly(o-ethylaniline) coatings were electrochemically synthesized on 304-stainless steel by using cyclic voltammetry from an aqueous salicylate medium. Cyclic voltammetry, UV-vis absorption spectroscopy, Fourier transform infrared spectroscopy and scanning electron microscopy were used to characterize these coatings, which indicates that the aqueous salicylate solution is a suitable medium for the electrochemical polymerization of o-ethyaniline on 304-stainless steel. The performance of poly(o-ethylaniline) as protective coating against corrosion of 304-stainless steel in aqueous 3% NaCl was evaluated by the open circuit potential measurements, potentiodynamic polarization technique, cyclic potentiodynamic polarization measurements and electrochemical impedance spectroscopy. The results of the potentiodynamic polarization and cyclic potentiodynamic polarization demonstrate that the poly(o-ethylaniline) coating provides excellent protection to both localized and general corrosion of 304-stainless steel. The corrosion potential was about 0.190 V more positive in aqueous 3% NaCl for the poly(o-ethylaniline) coated steel than that of bare steel and reduces the corrosion rate of steel almost by a factor of 20. (c) 2006 Elsevier B.V. All rights reserved.
Keywords: Conducting polymer coatings; Corrosion resistant coatings; cyclic voltammetry; Electrochemical polymerization; poly(o-ethylaniline) coatings; stainless steel

Synthesis of poly(aniline-co-o-toluidine) coatings and their corrosion-protection performance on low-carbon steel - Pawar, Pritee; Sainkar, S. R.; Patil, P. P. (Journal of Applied Polymer Science, 2007)
Strongly adherent poly(aniline-co-o-toluidine) coatings were synthesized on low-carbon-steel substrates by the electrochemical copolymerization of aniline with o-toluidine with sodium tartrate as the supporting electrolyte. These coatings were characterized with cyclic voltammetry, ultraviolet-visible absorption spectroscopy, Fourier transform infrared spectroscopy, nuclear magnetic resonance spectroscopy, and scanning electron microscopy. The formation of the copolymer with the mixture of monomers in the aqueous sodium tartrate solution was ascertained by a critical comparison of the results obtained from the polymerizations of the individual monomers, aniline and o-toluidine. The optical absorption spectrum of the copolymer was drastically different from the spectra of the respective homopolymers, polyaniline and poly(o-toluidine). The extent of the corrosion protection offered by poly(aniline-co-o-toluidine) coatings to low-carbon steel was investigated in aqueous 3% NaCl solutions by open-circuit-potential measurements and a potentiodynamic polarization technique. The results of the potentiodynamic polarization measurements showed that the poly(aniline-co-o-toluidine) coatings provided more effective corrosion protection to low-carbon steel than the respective homo-polymers. The corrosion rate depended on the feed ratio of o-toluidine used for the synthesis of the copolymer coatings. (c) 2006 Wiley Periodicals, Inc.
Keywords: Coatings; conducting polymers; copolymerization; synthesis

Use of poly(o-toluidine)/ZrO2 nanocomposite coatings for the corrosion protection of mild steel - Chaudhari, Sudeshna; Patil, P. P.; Mandale, A. B.; Patil, K. R.; Sainkar, S. R. (Journal of Applied Polymer Science, 2007)
This study explored the possibility of using poly(o-toluidine) (POT)/ZrO2 nanocomposite coatings for the corrosion protection of mild steel in a chloride environment. POT/ZrO2 nanocomposite coatings were synthesized on steel substrates through an electrochemical route. These coatings were characterized with cyclic voltammetry, ultraviolet-visible absorption spectroscopy, Fourier transform infrared spectroscopy, scanning electron microscopy, and X-ray photoelectron spectroscopy. The performance of POT/ZrO2 nanocomposites as protective coatings against the corrosion of mild steel in aqueous 3 wt % NaCl was evaluated with the potentiodynamic polarization technique and electrochemical impedance spectroscopy. The results of this study demonstrate that POT/ZrO2 nanocomposite coatings provide better protection for mild steel against corrosion than pure POT coatings. The corrosion potential was about 0.312 V versus a saturated calomel electrode, more positive in aqueous 3 wt % NaCl for the nanocomposite-coated steel than the uncoated steel, and the corrosion rate of steel was reduced by a factor of almost 51. (c) 2007 Wiley Periodicals, Inc.
Keywords: Coatings; conjugated polymers; FTIR; Nanocomposites; synthesis